2005
DOI: 10.1037/0022-0167.52.4.640
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Real Relationship in Psychotherapy: Initial Validation of the Therapist Form.

Abstract: The development and initial validation of a therapist-rated measure of the real relationship in psychotherapy (the Real Relationship Inventory-Therapist Form [RRI-T]) is reported. Using a sample (n ϭ 80) of practicing psychotherapists and on the basis of prior theory, the authors developed a 24-item measure consisting of 2 subscales (Realism and Genuineness) and a total score. This 24-item version and other measures used for validation were completed by 79 additional practicing therapists and 51 counseling gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(169 citation statements)
references
References 43 publications
(69 reference statements)
10
145
0
2
Order By: Relevance
“…In dit artikel wordt met het concept therapeutische alliantie verwezen naar zowel de band als de taken in de therapie. De band verwijst naar de persoonlijke relatie of hechting tussen therapeut en clie¨nt (Gelso e. a., 2005;Shelef e.a., 2005). Met de taak wordt gedoeld op de overeenstemming tussen therapeut en clie¨nt over de benodigde therapieactiviteiten die beiden dichter bij de therapiedoelen brengen (Bordin, 1979;Horvath & Luborsky, 1993).…”
Section: Niet-specifieke Factoren: Therapeutische Alliantieunclassified
“…In dit artikel wordt met het concept therapeutische alliantie verwezen naar zowel de band als de taken in de therapie. De band verwijst naar de persoonlijke relatie of hechting tussen therapeut en clie¨nt (Gelso e. a., 2005;Shelef e.a., 2005). Met de taak wordt gedoeld op de overeenstemming tussen therapeut en clie¨nt over de benodigde therapieactiviteiten die beiden dichter bij de therapiedoelen brengen (Bordin, 1979;Horvath & Luborsky, 1993).…”
Section: Niet-specifieke Factoren: Therapeutische Alliantieunclassified
“…For clinicians, self-disclosure is more frequently considered in relation to risk of boundary violation rather than being a positive opportunity to facilitate change. This softening of the clinician role to include sometimes being less role-based -and perhaps more 'real' (Gelso et al, 2005) -mirrors the change being asked of group participants, whose problems of course remain but are being invited to develop an identity as a person in recovery who can self-identify and use strengths (Davidson, Bellamy, Guy, & Miller, 2012).…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…Initial studies of the therapist version of the RRI revealed internal consistency at 0.89 for the total scale and 0.83 for the Genuineness portion (Gelso et al, 2005). It also had good concurrent validity when compared to measures of working alliance and session evaluation.…”
Section: Measures Of Genuinenessmentioning
confidence: 99%
“…These are the Relationship Inventory (BLRI; Barrett-Lennard, 1962), the Truax Relationship Questionnaire (TRQ; Lin, 1973), and the Real Relationship Inventory (RRI; Gelso et al, 2005). For purposes of succinctness, I will only detail these three measures.…”
Section: Measures Of Genuinenessmentioning
confidence: 99%
See 1 more Smart Citation